2016
DOI: 10.18084/1084-7219.21.1.79.
|View full text |Cite
|
Sign up to set email alerts
|

Beginning to See the Big Picture: BSW Student Reflections on Community Macro Practice

Abstract: This article describes an undergraduate social work macro practice course that included a service-learning project in which BSW students canvassed for a grassroots, community-based agency to increase voter participation in a low-income, disfranchised community. An analysis of students' reflections prior to and during the course and project illustrates how this experience cultivated students' perspectives about macro practice. Embedding a service-learning project into a macro practice course demystified this le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Unfortunately, macro social work is all too often siphoned off from micro and mezzo practice. As a result, many social workers are unable to immediately identify the connections between all forms of social work practice (Crutchfield et al, 2016;Lucero et al, 2017). Increased intentionality in social work education, through the MPA or similar learning activities, may help to reconnect these forms of practice in the minds of the next generation of social workers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, macro social work is all too often siphoned off from micro and mezzo practice. As a result, many social workers are unable to immediately identify the connections between all forms of social work practice (Crutchfield et al, 2016;Lucero et al, 2017). Increased intentionality in social work education, through the MPA or similar learning activities, may help to reconnect these forms of practice in the minds of the next generation of social workers.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found that roughly 42% of the student participants felt that instructors covered community practice course material insufficiently and that the material lacked the same depth as clinical material (Liddell & Lass, 2019). Although this is but one study, the results are troubling because the sample was comprised of students who evidenced some predisposition towards macro social work practice, rather than viewing it as a necessary educational nuisance on their way to a social work degree, as some social work students do (Crutchfield et al, 2016). Research has also found that macro practice students were often told by social work educators that it is difficult to obtain a job and pass the licensing exam with a concentration in macro practice -which perhaps speaks to the content of licensing exams (Plitt Donaldson et al, 2016).…”
Section: Students' Perceptions Of Macro Social Work Educationmentioning
confidence: 95%
See 2 more Smart Citations